Escape to the high canopy—thermal deficiency causes niche expansion in a forest‐floor ant. (21st June 2016) - Seifert, Bernhard; Fiedler, Patrick; Schultz, Roland
Abstract: The small formicoxenine ant Temnothorax saxonicus was known from about 40 localities in Central Europe nesting in anorganic substrates on floor of xerothermous forests whereas investigations of 198 tree canopies in 19 forest sites of the same region provided no indication for arboreal nesting or foraging. We present the first evidence for canopy‐nesting populations of T. saxonicus on old Quercus trees in 3 sites having maximum calibrated topsoil temperatures of 17.9 ± 0.3 °C which were significantly ( P < 0.007) lower than 22.8 ± 2.0 °C measured in 5 sites with ground‐nesting populations. The thermal deficit on forest floor inhibits brood development in ground nests and caused a moving to canopy were maximum calibrated temperatures of the, now wooden, substrates are at least 26.1 °C for the whole canopy and 30.8 °C in more sun‐exposed spots. T. saxonicus competed here successfully with the obligatory canopy ants T. affinis and T. corticalis . The distributional data of this rope‐climbing study support former results that highest nest densities of small arboreal ants occur in temperate climate over the entire canopy mantle of single trees situated in open land or in park‐like environments but occur in the top of the canopy in tree stands with high degree of canopy closure.